Pornography use in sexual minority males: Associations with body dissatisfaction, eating disorder symptoms, thoughts about using anabolic steroids and quality of life. (April 2018) - Griffiths, Scott; Mitchison, Deborah; Murray, Stuart B; Mond, Jonathan M
Objective: We examined two hypotheses regarding the potential association of pornography use with body image–related and eating disorder–related psychopathology among sexual minority males (i.e. non-heterosexual males). Our primary hypothesis was that pornography use would be associated with males' body dissatisfaction, eating disorder symptoms, thoughts about using anabolic steroids and quality of life impairment; our secondary hypothesis was that the type of pornography, namely, professional versus amateur pornography, which contains idealised and non-idealised (i.e. regular) bodies, respectively, would moderate these associations. Methods: A sample of 2733 sexual minority males living in Australia and New Zealand completed an online survey that contained measures of pornography use, body dissatisfaction, eating disorder symptoms, thoughts about using anabolic steroids and quality of life. Results: Almost all (98.2%) participants reported pornography use with a median use of 5.33 hours per month. Multivariate analyses revealed that increased pornography use was associated with greater dissatisfaction with muscularity, body fat and height; greater eating disorder symptoms; more frequent thoughts about using anabolic steroids; and lower quality of life. Effect sizes for these associations were uniformly small. Neither relationship status nor genital dissatisfaction was associated with pornography use. The association between pornography use and thoughts about using anabolic steroids was stronger for viewers of professional pornography than viewers of amateur pornography. Conclusion: The findings suggest that the use of pornography is weakly associated with body dissatisfaction and related variables and that the type of pornography (amateur vs professional) viewed may be a moderating factor in some cases. Within the limits of a cross-sectional study design, these findings may have implications for clinicians who treat individuals with eating disorders, body dysmorphic disorder, anabolic-androgenic steroid dependence and related concerns.